Teenage gambling in Australia - Saunders, Matt; Harrington, Morgan (My University, 2025)
Australians gamble more than any another nation. Gambling starts well before the age of 18 – almost one in three (30%) 12-17-year-olds gamble. This increases to almost half (46%) of 18-19-year-olds, and these habits persist into adulthood. Without greater regulation the losses associated with gambling are likely to grow.
Keywords: Adolescents and youth; Income, wealth and finances